Rockefeller Foundation funding and medical education in Toronto, Montreal and Halifax - Fedunkiw, Marianne P., 1965- (McGill-Queen's/Associated Medical Services (Hannah Institute) studies in the history of medicine, health, and society, 2005)
"This is the first book to look at how a major philanthropic donation transformed medical education in Canada. Marianne Fedunkiw demonstrates how sizable donations from the Rockefeller Foundation and the Eatons made possible the introduction of full-time clinical teaching and encouraged greater public and private support for medical education."--Jacket